Atividade antioxidante e antimicrobiana do alecrim (Rosmarinus officinalis L.) em filés de tilápia (Oreochromis ssp) salgados secos durante o armazenamento congelado - Afonso, M. S. [UNESP]; Sant'Ana, L. S. [UNESP]; Pinto, J. P A N [UNESP]; Ximenes, B. [UNESP] (My University, 2008)
Rosemary (Rosmarinus officinalis L.) is a spice from Lamiaceae family known since ancient times because its medicinal effects and, currently, several studies have pointed its antioxidant and antimicrobian effects. Lipid oxidation is a problem in food production because proceed the lost of organoleptical and nutritional qualities so required in Market. Fish salting is an ancient conservation method that expect reduce water activity and, consequently, microorganism growth in food, except halophillic bacteria. In the meantime, the inconvenient of this procedure is that the salt accelerates tissue's lipid oxidation. The aim of this work was evaluate the antioxidative and antimicrobian effects by treatment and pre treatment with rosemary (Rosmarinus officinalis L.) aqueous extract in dry salted tilapia fillets, storaged in freezing temperatures. To follow the oxidative, dry salted tilapia fillets were treated or pre treated with rosemary natural extract and storage at -18°C for 240 days. Analisys of 2-thiobarbituric acid reactive substances (TBARS), soluble nitrogen in trichloroacetic acid (TCA), water activity and microbiology were done. The pre treatment (3.39±0,53) and the treatment with rosemary (3.31±0.79) had oxidative index twice lower than the control treatment (6.14±1.21) in the last time of the research. The microbiological rosemary analisys showed count levels of resistant microorganisms to salt (2.0×103CFU/g of sample), whom causes the initial fillets contamination. The microbiological counts remained invariable in all groups during storage periods.
Antioxidant and antimicrobian activity of rosemary (Rosmarinus officinalis L.) in dry salted tilapia (Oreochromis ssp) fillets during freezing storage
Keywords: Halophillic bacteria; Lipid oxidation; Medicinal plants; Rosmarinus officinalis; Salting; Rosmarinus officinalis extract; sodium chloride; thiobarbituric acid reactive substance; trichloroacetic acid; antimicrobial activity; antioxidant activity; controlled study; freezing; germination; nonhuman; rosemary; Tilapia; Bacteria (microorganisms); Lamiaceae; Oreochromis